The nature of perceptual units in Chinese character recognition. Issue 8 (August 2022) - Isselé, Joanna; Chetail, Fabienne; Content, Alain
Chinese character recognition is based on a limited set of recurrent stroke patterns. Most Chinese characters are a combination of two or more of these components. To test whether readers are sensitive to combinations of components (or multi-component units [MCUs]) within a character, we conducted two probe detection tasks where participants had to detect the presence of a component in a target character. Critically, some targets contained an MCU that can stand as a character on its own, with its own meaning and sound, while other targets contained an MCU that only exists embedded within other characters (no associated meaning and sound). Participants had more difficulty detecting component probes that were a part of an existing MCU, compared to component probes that belonged to a non-existing MCU. These findings suggest that existing MCUs are a perceptual unit in Chinese character recognition.